0574 Prevalence and Characteristics of Rapid Eye Movement Obstructive Sleep Apnoea (REM OSA) in a Multi-Ethnic OSA Cohort. (27th May 2020) - Wong, H; Poh, Y; Mok, Y
Abstract: Introduction: Recent studies have shown that REM OSA is associated with increased incidence of hypertension and insulin resistance. However, there is a lack of Asian data on REM OSA. Our study aimed to examine the prevalence and characteristics of REM OSA in a multi-ethnic OSA cohort. Methods: This was a retrospective observational study of all patients who underwent an overnight diagnostic polysomnography at a Singapore tertiary hospital from 1st August 2017 to 31st August 2018. All patients with a diagnosis of OSA (Apnoea Hypopnea Index (AHI) ≥5) were included in the study. REM OSA is defined as an overall AHI≥5, REM AHI/Non REM (NREM) AHI>2, NREM AHI<15 and at least 15 minutes of REM sleep. Results: 457 OSA subjects were included in the analysis. 19% (87/457) had REM OSA. Univariate analysis showed that REM OSA was more prevalent among female OSA than male OSA [34/115 (29.6%) versus 53/342 (15.5%) respectively, p<0.001]. Compared to non REM OSA, REM OSA had milder OSA severity [mean AHI 12.74±4.71 versus 45.34±28.38, p<0.001] and lower prevalence of hypertension [21/87 (24.1%) versus 138/370(37.3%), p=0.02]. No differences were found between both groups for age (p=0.273), ethnicity (p=0.615), Body Mass Index (p=0.336), diabetes mellitus (p=0.245) and Epworth Sleepiness Scale (0.06). Gender and OSA severity differences between both groups remained statistically significant in multivariate analysis (higher prevalence of REM OSA in female, p=0.043 and milder disease severity in REM OSA, p=0.006). Conclusion: REM OSA was common in our OSA cohort and had higher prevalence in female and milder disease severity compared to non REM OSA. However, we did not find an increased prevalence of hypertension or diabetes mellitus in REM OSA. Further population-based study on REM OSA is needed to understand this phenotype better. Support: NIL